Image-based characterization of fibre waviness in a representative vacuum-bagged corner laminate. (April 2020) - Krumenacker, N.; Madra, A.; Hubert, P.
Abstract: The ability to fully characterize design-induced defects in complex-shape laminates is indispensable to improving the design and out-of-autoclave processing of large integrated structures. To this end, two automated methods are proposed to characterize fibre waviness in a representative vacuum-bagged corner laminate. The first relies on optical microscopy of corner-flange sections to estimate the extent to which corner waviness progresses into flanges. The second relies on X-ray micro computed tomography of corner sections and advanced image-based techniques to measure the waviness magnitude in terms of representative, in- and out-of-plane angular components. The 3D structure of the waviness is then ascertained based on the examination of the combined imaging results. Finally, the usefulness of the magnitude measurements is illustrated by estimating the knockdown in corner stiffness via an Euler angle transformation. Both characterization methods can be adapted to other, more complex-shape cases and alternate processing routes.